Study on static and dynamic performance of aircraft maintenance hangar under multiple load combinations. - Xiaolan Liu; Zhihua Chen; Fengheng Zhu; Hao Chen (PLoS ONE)
To analyze the collaborative work performance of the roof structure and the lower support structure for the aircraft maintenance hangar, a numerical model of a single-span aircraft maintenance hangar is established to study the static and dynamic mechanical responses under various load combinations. Results show that the primary axial force and bending moment responses are concentrated in the main truss and the lower support column. The maximum compression occurs at the upper section of the two main trusses, while the maximum tension appears at the mid-span of the lower inner truss near the hangar gate. The displacement of the main truss exceeds that of the secondary truss, with the roof's mid-span displacement being greater than that at the edges. The maximum support reactions occur at the main truss support column, the secondary truss column of the rear gable wall, and the lateral bracing between double-angle steel columns. The first three vibration modes and frequencies are highly susceptible to excitation and contribute significantly to the structure's seismic response. This study provides critical theoretical support for the design of large-span aircraft maintenance hangars. The findings can guide optimized design strategies to enhance structural safety and efficiency, contributing to advancements in long-span hangar construction and maintenance practices.